Kredyt bankowy jako kapitał obcy w finansowaniu potrzeb gospodarstw domowych - Mordarska, Dorota (My University, 2015)
Kredyt bankowy jest podstawowym obcym źródłem niesienia pomocy finansowej podmiotom gospodarczym. Instytucje bankowe upoważnione są w szczególności do udzielania kredytów bankowych zgodne z ustawą Prawa bankowego. Przy udzielaniu kredytu bankowego, banki stosują metody oceny zdolności i wiarygodności kredytowej przyszłego kredytobiorcy. Celem pracy była ocena wpływu kredytu bankowego na sytuację finansową i społeczną gospodarstw domowych. W części empirycznej pracy przeprowadzono za pomocą kwestionariusza ankiety analizę wpływu kredytu bankowego na sytuację finansową i społeczną gospodarstw domowych. Zweryfikowano cztery hipotezy badawcze. Były one podstawą do wyciągnięcia wniosków w zakresie wpływu kapitału obcego. Uzyskane wyniki pozwoliły ocenić wpływ kredytu bankowego na kondycję materialną gospodarstw domowych, a także na ich pozycję społeczną.

Bank credit is the main foreign source of giving financial support to many business entities. Banking institutions are specifically authorized to the provision of bank loans in accordance with the Banking Law Act. In granting bank loans, banks use methods of assessing the ability and creditworthiness of the future borrower. The aim of the study was to evaluate the influence of the bank credit on the financial and social situation of the households. Analysis of the influence of the bank credit on the financial and social situation of the households was included in the empirical part of the work. The mentioned analysis was conducted on the basis of the data taken from the survey. As a result of that analysis, four hypotheses were distinguished. They became the basis for drawing conclusions regarding the impact of the foreign capital. The results allowed to assess the impact of bank credit on the condition of households, as well as their social position.
Bank credit as foreign capital in the financing the needs of the households
Keywords: kredyt bankowy; ryzyko kredytowe; gospodarstwo domowe; bankowość detaliczna; zdolność kredytowa; wiarygodność kredytowa; bank loan; credit risk; household; retail banking; creditworthiness; reliability credit